2018
DOI: 10.3168/jds.2017-13605
|View full text |Cite
|
Sign up to set email alerts
|

Replacing maize silage plus soybean meal with red clover silage plus wheat in diets for lactating dairy cows

Abstract: The objectives of this study were to evaluate the effects of replacing maize silage plus soybean meal with red clover silage (RCS) plus wheat on feed intake, diet digestibility, N partitioning, urinary excretion of purine derivatives, and milk production in dairy cows. Forty-four lactating German Holstein cows were used in a 4 × 4 Latin square design with 21-d periods composed of a 13-d adaptation phase followed by an 8-d sampling phase. Experimental diets offered as total mixed ration consisted of a constant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
36
1
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(44 citation statements)
references
References 38 publications
6
36
1
1
Order By: Relevance
“…where DMI is in kg/d and is that reported by Schulz et al [16], the ME is metabolizable energy content of the TMR in MJ/kg DM, estimated in vitro (RCS15 = 11.6, RCS30 = 11.4, RCS45 = 10.9, RCS60 = 10.7; [25]), 10.1 is the assumed value of MCP efficiency in g/MJ ME according to German protein evaluation system [26], OMI is organic matter (OM) intake in kg/d, ATTDOM is the apparent total tract digestibility of OM reported by Schulz et al [16], and 156 is the assumed value of MCP efficiency in g/kg digestible OM according to GfE [26]. All statistical analyses were conducted using the software R (version 3.1.0, The R Foundation for Statistical Computing; Vienna, Austria).…”
Section: Calculations and Statistical Analysismentioning
confidence: 95%
See 4 more Smart Citations
“…where DMI is in kg/d and is that reported by Schulz et al [16], the ME is metabolizable energy content of the TMR in MJ/kg DM, estimated in vitro (RCS15 = 11.6, RCS30 = 11.4, RCS45 = 10.9, RCS60 = 10.7; [25]), 10.1 is the assumed value of MCP efficiency in g/MJ ME according to German protein evaluation system [26], OMI is organic matter (OM) intake in kg/d, ATTDOM is the apparent total tract digestibility of OM reported by Schulz et al [16], and 156 is the assumed value of MCP efficiency in g/kg digestible OM according to GfE [26]. All statistical analyses were conducted using the software R (version 3.1.0, The R Foundation for Statistical Computing; Vienna, Austria).…”
Section: Calculations and Statistical Analysismentioning
confidence: 95%
“…The animal study reported herein was performed in accordance with the German Animal Welfare Act [17] and was approved by the Animal Welfare Commission of the Ministry of Energy, Agriculture, Environment, and Rural Areas of the Federal State of Schleswig-Holstein, Germany (V 242-72241.123 -5). The data presented in this study were derived from a feeding trial described by Schulz et al [16,18]. Succinctly, 44 German Holstein cows were used for the experiment.…”
Section: Animals Diets and Experimental Designmentioning
confidence: 99%
See 3 more Smart Citations